FAKTOR-FAKTOR YANG MEMPENGARUHI CALON PENGANTIN (CATIN) DALAM MELAKUKAN PEMERIKSAAN KESEHATAN PRANIKAH DI KECAMATAN ALAM BARAJO KOTA JAMBI TAHUN 2026 - Awalitus .usnul (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2026)
Premarital screening is a health checkup recommended for couples before marriage. Data from the National Population and Family Planning Board (BKKBN) in 2023 shows that premarital health checkup coverage in Indonesia only reached 39.7% of the national target of 80%. In 2023, 17,346 prospective brides and grooms underwent health checks, while in 2024, that number increased to 28,390. Alam Barajo District is one of the most populous areas in Jambi City, with approximately 18.3% of the city's population. This condition shows the high potential for marriage and the need for attention to the health readiness of prospective brides and grooms. The population in this study was prospective brides and grooms (catin) who were registered and underwent a premarital health check-up process in the Alam Barajo District, Jambi City in 2025, amounting to 125 people with a sample size of 56 people. Data were collected through interviews using a questionnaire instrument. To find out the factors that influence prospective brides and grooms in conducting premarital health checks, chi-square statistical analysis was used. Data analysis consisted of univariate and bivariate analysis. The results of the study showed that there was a relationship between the knowledge of prospective brides and grooms with premarital health check behavior (p value = 0.000), family support (p value = 0.032), accessibility (p value = 0.011), there was no relationship between the attitude of prospective brides and grooms with premarital health check behavior (p value = 0.299) and there was no relationship between government program policies (p value = 0.222).